Pivotal Decision for Acute Coronary Syndrome Patient with Left Main Coronary Artery Disease, When to Choose PCI over CABG - Setyowati, Danti Utami; Rohman, Mohammad Saifur; Prasetya, Indra (Heart Science Journal, 2024)
Background: Surgery is acceptable as a standard treatment of Left Main Coronary Artery (LMCA) Disease in a stable angina condition. But, in Acute Coronary Syndrome (ACS) setting, LMCA intervention is a still clinical challenge in many cardiac centers. Percutaneous coronary intervention (PCI) has emerged as a suitable alternative to coronary artery bypass grafting (CABG) for high-risk complex coronary artery disease (CAD) scenario. This study aimed to outline the management of NSTEMI patient include LMCA disease. Case Report: A 72-year-old male presented with persistent chest pain, with a confirmed NSTEMI. A coronary angiography was done and revealed Three Vessel Disease (TVD) and Left Main (LM) CAD with highly calcified stenosis in the distal LM and Left Anterior Descending (LAD). An early invasive procedure was successfully performed for severely calcified LAD artery and distal LM lesions, using proper selection of several bail-out pre-dilatation difficult attempts such as scoring ballon and rotational atherectomy (RA). We observed the aftercare period, which showed no subsequent ACS events. Conclusion: Managing ACS patients requires careful consideration and risk assessment before deciding on revascularization procedures, especially in high-risk case such as LMCA disease. PCI can be an effective treatment strategy for this population but require good consideration of patient’s anatomical factors, comorbidities, the availability of appropriate skill and equipment.